Institutional change and productivity growth in China's manufacturing 1998-2007: The microeconomics of creative restructuring - Giovanni Dosi; Jiasu Lei; Xiaodan Yu (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2013)
This paper investigates firm-level dynamics of labour productivity in China's manufacturing sector over the 1998-2007. Underlying the aggregate evidence of dramatic growth of labour productivity, one observes a large, even if shrinking, intra-sectoral heterogeneity. A major process of both catching-up and dying out occurs among the least efficient ones. Furthermore, we explore the effect of the characteristics of firms according to the ownership and governance structure upon the productivity distributions. The transformation of domestic firms significantly affect the decreasing dispersion of productivity. In essence the fast catching-up process entails more of a creative restructuring of domestic firms rather than sheer creative destruction and even less so an MNC-led drive.
Keywords: O1; O3; O4; 330; Chinese industrial development; labour productivity distributions; catching-up; heterogeneity; corporate ownership